2003
DOI: 10.5713/ajas.2003.719
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Calcium and Non-phytin Phosphorus Interaction on Growth, Bone Mineralization and Mineral Retention in Broiler Starter Chicks

Abstract: An experiment was conducted to study the requirement of calcium (Ca) and non-phytin phosphorus (NPP) in commercial broilers during starter phase. Seven hundred and twenty day-old Vencob male broiler chicks were randomly distributed into 144 stainless steel battery brooders, 5 birds in each. Four levels each of Ca (6, 7, 8, and 9 g/kg) and NPP (3, 3.5, 4, and 4.5 g/kg diet) were fed in a factorial design in a corn-soya basal diet. Levels of dicalcium phosphate and oyster shell grit were adjusted to obtain the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…(2017) , who found that broilers fed with 0.23% NPP diet had lower tibia BMD, BBS, and ash content than the control broilers. Rama Rao et al. (2003) also found that a decrease of Ca and NPP levels in the broiler diet had a negative effect on tibia BBS and ash content.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…(2017) , who found that broilers fed with 0.23% NPP diet had lower tibia BMD, BBS, and ash content than the control broilers. Rama Rao et al. (2003) also found that a decrease of Ca and NPP levels in the broiler diet had a negative effect on tibia BBS and ash content.…”
Section: Discussionmentioning
confidence: 78%
“…Many studies demonstrated that the bone development parameters, such as tibia BMD, BBS, and ash content of broilers, were susceptible to dietary Ca or P level ( Williams et al., 2000a , Rama Rao et al., 2003 , Liu et al., 2017 ). Results from the present study showed that the Ca- or P-deficient diets negatively affected the tibia BMD, BBS, and ash content of broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Hulan et al [25] found that the dietary Ca:nPP above 2.81:1 could depress the growth performance and FI in broilers. And Rama Rao et al [26] also observed that broilers fed diets with 2.3–3:1 Ca:nPP had poor performance. Because the two minerals tend to form calcium phosphate, an insoluble complex in the chicken gut resulting in reduced absorption, which may be the reason for growth retardation at higher Ca:nPP [27].…”
Section: Discussionmentioning
confidence: 99%
“…Feeding heifers 0.39% P also increased (P < 0.01) bone Cu content compared with feeding heifers 0.29% P. Bovine bone contains approximately 10 μg of copper per g (Doyle, 1979) on an ash basis and copper plays an important role in collagen maturation linked to its function as a cofactor in lysyl oxidase (Turnlund, 2006). Increasing dietary P from nonphytin sources can adversely affect Cu bioavailability by increasing Cu excretion (Rama Rao et al, 2003), but that does not explain lower bone Cu content observed in this study when heifers were fed diets containing 0.29% P compared with feeding heifers 0.39% P. Prince et al (1984) reported increased levels of liver Cu when pigs were fed high levels of dietary P (>1.00) but could not discount potential Cu contamination in P supplements used to alter dietary P. Likewise, in this study the need for intensive measurement of dietary Cu was not foreseen and thus not undertaken; therefore, dietary influences in regard to differences in bone Cu content observed in this study cannot be dismissed.…”
Section: Discussionmentioning
confidence: 99%